A preparation process of composite material based on resin transfer film

By using the photocuring technology of water-based acrylic adhesive and resin transfer film on glass substrate, the existing problem of insufficient adhesion strength is solved, and a composite material with high adhesion, high temperature and water resistance is realized , improves the performance and efficiency of the imprinting technology.

CN118991054BActive Publication Date: 2025-02-25LONGKOU KENUOER GLASS TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411455498.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-25
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The adhesion of existing water sols is weak and cannot meet the requirements of high temperature and water resistance, making it difficult to achieve strong adhesion, high temperature and water resistance in the imprinting technology.

Method used

Using a composite material preparation process based on resin transfer film, the resin transfer film is closely combined with the glass by coating aqueous acrylic adhesive on the glass substrate, and using photocuring technology to closely combine the resin transfer film with glass to form a high adhesion and resistance. A composite material with high temperature and water resistance.

Benefits of technology

The glass substrate surface has higher adhesion, high temperature resistance, water resistance and scratch resistance, improved production efficiency and provided a wider selection of pattern types.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118991054B_ABST
    Figure CN118991054B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of imprinting technology, and specifically to a preparation process of a composite material based on a resin transfer film, comprising the following steps: Step 1, cleaning the surface of a glass substrate to be treated; Step 2, selecting a suitable resin transfer film, and processing the resin transfer film according to the required shape and size; Step 3, coating the surface of the substrate treated in Step 1 with a layer of adhesive; Step 4, attaching the resin transfer film to the adhesive of the glass substrate and curing it; Step 5, trimming, polishing and painting as needed to obtain the final product. The glass and the resin film of the present invention have a special adhesive adhesion, which not only allows for more pattern types, but also has better adhesion, high temperature resistance, water resistance and scratch resistance; and the curing of the process of the present invention uses UV light curing, and the overall production efficiency is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of embossing, and in particular to a preparation process of a composite material based on a resin transfer film. Background Art

[0002] The existing glass micro-nano imprinting technology is a manufacturing method that transfers micron and nanometer-scale patterns to the glass surface. It is a high-precision processing technology that can create tiny structures and patterns on the glass surface. Micro-nano imprinting technology has the advantages of low manufacturing cost, high output, and a wide range of applicable materials. It has become a research hotspot in the field of micro-nano manufacturing. At present, micro-nano imprinting technology has been widely used in the electronics industry, biomedicine, aerospace and other fields.

[0003] Adhesives are usually used in embossing technology. Adhesives must have high adhesion, high temperature resistance, scratch resistance, water resistance, cooking resistance and chemical resistance. The most commonly used adhesive is oily glue, which is a kind of glue with high viscosity and strong adhesion. It needs to be diluted before use and has the advantage of good printing effect. However, the organic solvents volatilized by oily glue are harmful to human health, so new hydrosols have gradually emerged to replace oil sols. However, the adhesion of hydrosols currently on the market is weak, and the water resistance and high temperature resistance cannot meet the needs. Therefore, it is currently urgent to find a hydrosol with strong adhesion, water resistance and high temperature resistance. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a preparation process of a composite material based on resin transfer.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] A preparation process of a composite material based on a resin transfer film comprises the following steps:

[0007] Step 1, performing surface cleaning treatment on the glass substrate to be treated;

[0008] Step 2, selecting a suitable resin transfer film and processing the resin transfer film according to the required shape and size;

[0009] Step 3, coating a layer of adhesive on the surface of the substrate treated in step 1;

[0010] Step 4, laminating the resin transfer film of step 2 on the adhesive of the glass substrate, and making it closely bonded to the glass substrate by a photocuring method;

[0011] Step 5: Finish, sand and paint as needed to get the final product.

[0012] Preferably, the surface cleaning in step 1 is firstly cleaned with deionized water and then with anhydrous ethanol, and the cleaning is all carried out in an ultrasonic device with a cleaning frequency of 20-30 kHz.

[0013] Preferably, the material of the resin transfer film in step 2 is one of PE, PVC, PET and PC.

[0014] Preferably, during the light curing process in step 4, the wavelength of the ultraviolet light is 365nm and the radiation amount is 100-200mW / cm 2 , the curing time is 1-5min.

[0015] Preferably, the adhesive in step 3 is a water-based acrylic adhesive, which comprises, by weight:

[0016] 50-60 parts of acrylic monomer, 6-12 parts of triazine compound containing vinyl, 2.1-4.2 parts of emulsifier, 0.5-1 parts of crosslinking agent, 0.1-0.5 parts of initiator, 0.05-0.1 parts of photosensitizer, 0.2-0.6 parts of defoamer, 0.3-0.6 parts of leveling agent, 0.1-0.3 parts of neutralizer and 55-75 parts of deionized water.

[0017] Preferably, the acrylic monomers include acrylic acid, methyl acrylate, methyl methacrylate, lauryl acrylate, and tetrahydrofuran methacrylate in a mass ratio of 0.5-1:0.2-0.6:0.3-0.8:0.6-1.2:0.4-0.8.

[0018] Preferably, the preparation method of the triazine compound containing vinyl group comprises:

[0019] Weigh 3-methyl-2-butenal and 2-amino-1,3,5-triazine, mix them in toluene, stir them thoroughly until they are uniform, heat them to 80-100° C. under the action of a catalyst, stir them for 3-8 hours, and then perform rotary evaporation to remove impurities to obtain a triazine compound containing a vinyl group.

[0020] Preferably, in the preparation of the triazine compound containing vinyl group, the catalyst is glacial acetic acid, and the added amount is 2%-6% of the mass of 2-amino-1,3,5-triazine.

[0021] Preferably, in the preparation of the triazine compound containing vinyl, the mass ratio of 3-methyl-2-butenal, 2-amino-1,3,5-triazine and toluene is 1.1-1.4:0.8-1.2:20-50.

[0022] Preferably, the emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate and sodium hexadecylbenzene sulfonate.

[0023] Preferably, the crosslinking agent is tripropylene glycol diacrylate or 1,6-hexanediol diacrylate.

[0024] Preferably, the initiator is at least one of sodium persulfate, potassium persulfate and ammonium persulfate.

[0025] Preferably, the photosensitizer is at least one of photosensitizer 1173 , photosensitizer 819 , photosensitizer 184 , and photosensitizer 907 .

[0026] Preferably, the defoaming agent is at least one of Dego 810, Dego 825, Dego 901W and Dego 902W.

[0027] Preferably, the leveling agent is at least one of BYK-333, BYK-378 and BYK-381.

[0028] Preferably, the neutralizing agent is triethylamine or ethanolamine.

[0029] Preferably, the preparation process of the water-based acrylic adhesive comprises:

[0030] S1, weighing an acrylic monomer, a triazine compound containing a vinyl group, an emulsifier and deionized water, mixing them, stirring them thoroughly until they are uniform, and then dividing them into two parts, namely a first acrylic emulsion and a second acrylic emulsion;

[0031] S2, heating the first acrylic emulsion to 75-85° C., stirring at this temperature for 10-20 min, then adding a crosslinking agent, and continuing stirring at this temperature for 10-20 min to obtain a third acrylic emulsion;

[0032] S3, adding an initiator to the second acrylic emulsion, stirring it evenly, and then adding it dropwise to the third acrylic emulsion, the dropping time is controlled to be 1-2 hours, then heating to 85-95° C., stirring for 2-3 hours, and then cooling to room temperature to obtain a fourth acrylic emulsion;

[0033] S4. Add a photosensitizer, a defoamer and a leveling agent to the fourth acrylic emulsion, protect from light and stir thoroughly, then add a neutralizer to adjust the pH to obtain a water-based acrylic adhesive.

[0034] The beneficial effects of the present invention are:

[0035] 1. Compared with the traditional process technology, the composite material process of the present invention has a more flexible structural combination. There is a special adhesive bonding between the glass and the resin film, which not only can have more pattern types, but also has good adhesion, high temperature resistance, water resistance and scratch resistance; and the curing of the process of the present invention adopts UV light curing, and the overall production efficiency is also improved.

[0036] 2. The adhesive used in the present invention is an environmentally friendly water-based acrylic adhesive, which uses acrylic monomers and triazine compounds containing vinyl groups as main raw materials and is prepared by cross-linking polymerization in an aqueous solution. In this process, a variety of additives are added as auxiliary materials, and the triazine compound containing vinyl groups is used as a monomer to participate in the polymerization process of acrylic monomers. Compared with the adhesive prepared from pure acrylic monomers, the adhesive prepared and synthesized by the present invention has better adhesion, high temperature resistance, water resistance and scratch resistance.

[0037] 3. The triazine compound containing vinyl is synthesized by using 3-methyl-2-butenal containing aldehyde group and 2-amino-1,3,5-triazine containing amino group through amine-aldehyde reaction. The obtained product contains not only vinyl group but also Schiff base structure synthesized by amino group and aldehyde group. The product is used as a monomer to emulsion polymerize with acrylic monomer to obtain water-based acrylic adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0039] Figure 1 This is a process flow chart for preparing a composite material according to Example 1 of the present invention. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0041] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0042] The present invention will be further described below in conjunction with the following examples.

[0043] Example 1

[0044] A preparation process of a composite material based on a resin transfer film, such as Figure 1 As shown, the following steps are included:

[0045] Step 1, the surface of the glass substrate to be treated is cleaned in an ultrasonic device, first with deionized water and then with anhydrous ethanol, with a cleaning frequency of 25kHz;

[0046] Step 2, selecting a PET resin transfer film and processing the resin transfer film according to the required shape and size;

[0047] Step 3, coating the surface of the substrate treated in step 1 with a layer of water-based acrylic adhesive;

[0048] Step 4: Lay the resin transfer film of step 2 on the adhesive of the glass substrate and make it closely bonded to the glass substrate by photocuring. The conditions of photocuring are: the wavelength of ultraviolet light is 365nm and the radiation amount is 150mW / cm 2 , curing time is 3min;

[0049] Step 5: Finish, sand and paint as needed to get the final product.

[0050] The above-mentioned water-based acrylic adhesive, calculated by weight, includes:

[0051] 55 parts of acrylic monomer, 8 parts of triazine compound containing vinyl, 3.2 parts of emulsifier, 0.6 parts of crosslinking agent, 0.3 parts of initiator, 0.07 parts of photosensitizer, 0.4 parts of defoamer, 0.5 parts of leveling agent, 0.2 parts of neutralizer and 65 parts of deionized water.

[0052] The acrylic monomers include acrylic acid, methyl acrylate, methyl methacrylate, lauryl acrylate and tetrahydrofuran methacrylate in a mass ratio of 0.6:0.4:0.5:0.9:0.6.

[0053] Wherein, the preparation method of the triazine compound containing vinyl group comprises:

[0054] Weigh 3-methyl-2-butenal and 2-amino-1,3,5-triazine and mix them in toluene. The mass ratio of 3-methyl-2-butenal, 2-amino-1,3,5-triazine and toluene is 1.2:1:30. After fully stirring until uniform, heat to 90°C under the action of glacial acetic acid and stir for 5 hours. The amount of glacial acetic acid added is 4% of the mass of 2-amino-1,3,5-triazine. Then, rotary evaporation is performed to remove impurities to obtain a triazine compound containing vinyl.

[0055] Among them, the emulsifier is sodium dodecyl sulfate, the cross-linking agent is tripropylene glycol diacrylate, the initiator is sodium persulfate, the photosensitizer is photosensitizer 1173, the defoaming agent is Digo 810, the leveling agent is BYK-333, and the neutralizer is ethanolamine.

[0056] The preparation process of the above-mentioned water-based acrylic adhesive comprises:

[0057] S1, weighing an acrylic monomer, a triazine compound containing a vinyl group, an emulsifier and deionized water, mixing them, stirring them thoroughly until they are uniform, and then dividing them into two parts, namely a first acrylic emulsion and a second acrylic emulsion;

[0058] S2, heating the first acrylic emulsion to 80° C., stirring at this temperature for 15 min, then adding a crosslinking agent, and continuing stirring at this temperature for 15 min to obtain a third acrylic emulsion;

[0059] S3, adding an initiator to the second acrylic emulsion, stirring it evenly, and then adding it dropwise to the third acrylic emulsion, the dropping time is controlled to be 1.5 hours, then heating to 90° C., stirring for 2.5 hours, and then cooling to room temperature to obtain a fourth acrylic emulsion;

[0060] S4. Add a photosensitizer, a defoamer and a leveling agent to the fourth acrylic emulsion, protect from light and stir thoroughly, then add a neutralizer to adjust the pH to obtain a water-based acrylic adhesive.

[0061] Example 2

[0062] A preparation process of a composite material based on a resin transfer film comprises the following steps:

[0063] Step 1, the surface of the glass substrate to be treated is cleaned in an ultrasonic device, first with deionized water and then with anhydrous ethanol, with a cleaning frequency of 20 kHz;

[0064] Step 2, select a PE resin transfer film and process the resin transfer film according to the required shape and size;

[0065] Step 3, coating the surface of the substrate treated in step 1 with a layer of water-based acrylic adhesive;

[0066] Step 4: Lay the resin transfer film of step 2 on the adhesive of the glass substrate and make it closely bonded to the glass substrate by photocuring. The conditions of photocuring are: the wavelength of ultraviolet light is 365nm and the radiation amount is 100mW / cm 2 , curing time is 1min;

[0067] Step 5: Finish, sand and paint as needed to get the final product.

[0068] The above-mentioned water-based acrylic adhesive, calculated by weight, includes:

[0069] 50 parts of acrylic monomer, 6 parts of triazine compound containing vinyl, 2.1 parts of emulsifier, 0.5 parts of crosslinking agent, 0.1 parts of initiator, 0.05 parts of photosensitizer, 0.2 parts of defoamer, 0.3 parts of leveling agent, 0.1 parts of neutralizer and 55 parts of deionized water.

[0070] The acrylic monomers include acrylic acid, methyl acrylate, methyl methacrylate, lauryl acrylate and tetrahydrofuran methacrylate in a mass ratio of 0.5:0.2:0.3:0.6:0.4.

[0071] The preparation method of the triazine compound containing vinyl group comprises:

[0072] Weigh 3-methyl-2-butenal and 2-amino-1,3,5-triazine and mix them in toluene. The mass ratio of 3-methyl-2-butenal, 2-amino-1,3,5-triazine and toluene is 1.1:0.8:20. After fully stirring until uniform, heat to 80°C under the action of glacial acetic acid and stir for 3 hours. The amount of glacial acetic acid added is 2% of the mass of 2-amino-1,3,5-triazine. Then, rotary evaporation is performed to remove impurities to obtain a triazine compound containing vinyl.

[0073] The emulsifier is sodium dodecylbenzene sulfonate, the cross-linking agent is 1,6-hexanediol diacrylate, the initiator is potassium persulfate, the photosensitizer is photosensitizer 819, the defoaming agent is Digo 825, the leveling agent is BYK-378, and the neutralizer is triethylamine.

[0074] The preparation process of the above-mentioned water-based acrylic adhesive comprises:

[0075] S1, weighing an acrylic monomer, a triazine compound containing a vinyl group, an emulsifier and deionized water, mixing them, stirring them thoroughly until they are uniform, and then dividing them into two parts, namely a first acrylic emulsion and a second acrylic emulsion;

[0076] S2, heating the first acrylic emulsion to 75° C., stirring at this temperature for 10 min, then adding a crosslinking agent, and continuing stirring at this temperature for 10 min to obtain a third acrylic emulsion;

[0077] S3, adding an initiator to the second acrylic emulsion, stirring it evenly, and then adding it dropwise to the third acrylic emulsion, the dropping time is controlled to be 1 hour, then heating to 85° C., stirring for 2 hours, and then cooling to room temperature to obtain a fourth acrylic emulsion;

[0078] S4. Add a photosensitizer, a defoamer and a leveling agent to the fourth acrylic emulsion, protect from light and stir thoroughly, then add a neutralizer to adjust the pH to obtain a water-based acrylic adhesive.

[0079] Example 3

[0080] A preparation process of a composite material based on a resin transfer film comprises the following steps:

[0081] Step 1, the surface of the glass substrate to be treated is cleaned in an ultrasonic device, firstly with deionized water and then with anhydrous ethanol, and the cleaning frequency is 30kHz;

[0082] Step 2, selecting a PVC resin transfer film and processing the resin transfer film according to the required shape and size;

[0083] Step 3, coating the surface of the substrate treated in step 1 with a layer of water-based acrylic adhesive;

[0084] Step 4: Lay the resin transfer film of step 2 on the adhesive of the glass substrate and make it closely bonded to the glass substrate by light curing. The conditions of light curing are: the wavelength of ultraviolet light is 365nm and the radiation amount is 200mW / cm 2 , curing time is 5min;

[0085] Step 5: Finish, sand and paint as needed to get the final product.

[0086] The above-mentioned water-based acrylic adhesive, calculated by weight, includes:

[0087] 60 parts of acrylic monomer, 12 parts of triazine compound containing vinyl, 4.2 parts of emulsifier, 1 part of cross-linking agent, 0.5 parts of initiator, 0.1 parts of photosensitizer, 0.6 parts of defoamer, 0.6 parts of leveling agent, 0.3 parts of neutralizer and 75 parts of deionized water.

[0088] The acrylic monomers include acrylic acid, methyl acrylate, methyl methacrylate, lauryl acrylate and tetrahydrofuran methacrylate in a mass ratio of 1:0.6:0.8:1.2:0.8.

[0089] Wherein, the preparation method of the triazine compound containing vinyl group comprises:

[0090] Weigh 3-methyl-2-butenal and 2-amino-1,3,5-triazine and mix them in toluene. The mass ratio of 3-methyl-2-butenal, 2-amino-1,3,5-triazine and toluene is 1.4:1.2:50. After fully stirring until uniform, heat to 100°C under the action of glacial acetic acid and stir for 8 hours. The amount of glacial acetic acid added is 6% of the mass of 2-amino-1,3,5-triazine. Then, perform rotary evaporation to remove impurities to obtain a triazine compound containing vinyl.

[0091] The emulsifier is sodium hexadecyl sulfate, the cross-linking agent is tripropylene glycol diacrylate, the initiator is ammonium persulfate, the photosensitizer is photosensitizer 184, the defoaming agent is Digo 901W, the leveling agent is BYK-381, and the neutralizer is triethylamine.

[0092] The preparation process of the above-mentioned water-based acrylic adhesive comprises:

[0093] S1, weighing an acrylic monomer, a triazine compound containing a vinyl group, an emulsifier and deionized water, mixing them, stirring them thoroughly until they are uniform, and then dividing them into two parts, namely a first acrylic emulsion and a second acrylic emulsion;

[0094] S2, heating the first acrylic emulsion to 85° C., stirring at this temperature for 20 min, then adding a crosslinking agent, and continuing stirring at this temperature for 20 min to obtain a third acrylic emulsion;

[0095] S3, adding an initiator to the second acrylic emulsion, stirring it evenly, and then adding it dropwise to the third acrylic emulsion, the dropping time is controlled to be 2 hours, then heating to 95° C., stirring for 3 hours, and then cooling to room temperature to obtain a fourth acrylic emulsion;

[0096] S4. Add a photosensitizer, a defoamer and a leveling agent to the fourth acrylic emulsion, protect from light and stir thoroughly, then add a neutralizer to adjust the pH to obtain a water-based acrylic adhesive.

[0097] Comparative Example 1

[0098] A preparation process of a composite material based on a resin transfer film, which is different from Example 1 in that the composition of the water-based acrylic adhesive is different, and the difference is that the triazine compound containing vinyl is replaced by acrylic acid. That is, the water-based acrylic adhesive of this comparative example, calculated by weight, includes:

[0099] 55 parts of acrylic monomer, 8 parts of acrylic acid, 3.2 parts of emulsifier, 0.6 parts of crosslinking agent, 0.3 parts of initiator, 0.07 parts of photosensitizer, 0.4 parts of defoamer, 0.5 parts of leveling agent, 0.2 parts of neutralizer and 65 parts of deionized water.

[0100] Comparative Example 2

[0101] A preparation process of a composite material based on a resin transfer film, which is different from Example 1 in that the composition of the water-based acrylic adhesive is different, and the difference is that the triazine compound containing vinyl is replaced by 2-amino-1,3,5-triazine. That is, the water-based acrylic adhesive of this comparative example, calculated by weight, includes:

[0102] 55 parts of acrylic monomer, 8 parts of 2-amino-1,3,5-triazine, 3.2 parts of emulsifier, 0.6 parts of crosslinking agent, 0.3 parts of initiator, 0.07 parts of photosensitizer, 0.4 parts of defoamer, 0.5 parts of leveling agent, 0.2 parts of neutralizer and 65 parts of deionized water.

[0103] Comparative Example 3

[0104] A preparation process of a composite material based on a resin transfer film, which is different from Example 1 in that the composition of the water-based acrylic adhesive is different, and the difference is that the triazine compound containing vinyl is replaced by 3-methyl-2-butenal. That is, the water-based acrylic adhesive of this comparative example, calculated by weight, includes:

[0105] 55 parts of acrylic monomer, 8 parts of 3-methyl-2-butenal, 3.2 parts of emulsifier, 0.6 parts of crosslinking agent, 0.3 parts of initiator, 0.07 parts of photosensitizer, 0.4 parts of defoamer, 0.5 parts of leveling agent, 0.2 parts of neutralizer and 65 parts of deionized water.

[0106] The performance of the water-based acrylic adhesive layer of the composite materials prepared in Example 1 and Comparative Examples 1-3 was tested and compared, including adhesion, Shore A hardness, tensile shear strength, high temperature resistance and water resistance. The adhesion test reference standard GB / T 9286-2021; the hardness test reference standard GB / T 2411-2008; the tensile shear strength test reference standard GB / T 7124-2008; the high temperature resistance test was performed by treating at 150°C for 48 hours and then placing at room temperature, and then testing the change rate of tensile shear strength. The water resistance test was performed by immersing in water for 168 hours and then air-drying for 2 hours, and then testing the change rate of tensile shear strength.

[0107] The test results are shown in Table 1:

[0108] Table 1 Performance test of different adhesives

[0109]

[0110] It can be seen from Table 1 that the water-based acrylic adhesive layer prepared in Example 1 of the present invention has high adhesion and high hardness, indicating that its adhesion and scratch resistance are good. In addition, the adhesive of Example 1 has higher tensile shear strength, and the rate of change after high temperature treatment or immersion treatment is smaller, indicating that its strength is higher, and its water resistance and high temperature resistance are better.

[0111] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0112] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A process for preparing a composite material based on a resin transfer film, characterized in that: The following steps are involved: Step 1, performing surface cleaning treatment on the glass substrate to be treated; Step 2, selecting a suitable resin transfer film and processing the resin transfer film according to the required shape and size; Step 3, coating a layer of adhesive on the surface of the substrate treated in step 1; Step 4, laminating the resin transfer film of step 2 on the adhesive of the glass substrate, and making it closely bonded to the glass substrate by a photocuring method; Step 5: Perform trimming, sanding and painting as needed to obtain the final product; The adhesive in step 3 is a water-based acrylic adhesive, which comprises, by weight: 50-60 parts of acrylic monomer, 6-12 parts of triazine compound containing vinyl, 2.1-4.2 parts of emulsifier, 0.5-1 parts of crosslinking agent, 0.1-0.5 parts of initiator, 0.05-0.1 parts of photosensitizer, 0.2-0.6 parts of defoamer, 0.3-0.6 parts of leveling agent, 0.1-0.3 parts of neutralizer and 55-75 parts of deionized water; The preparation process of the water-based acrylic adhesive comprises: S1, weighing an acrylic monomer, a triazine compound containing a vinyl group, an emulsifier and deionized water, mixing them, stirring them thoroughly until they are uniform, and then dividing them into two parts, namely a first acrylic emulsion and a second acrylic emulsion; S2, heating the first acrylic emulsion to 75-85° C., stirring at the temperature for 10-20 min, then adding a crosslinking agent, and continuing stirring at the temperature for 10-20 min to obtain a third acrylic emulsion; S3, adding an initiator to the second acrylic emulsion, stirring it evenly, and then adding it dropwise to the third acrylic emulsion, the dropping time is controlled to be 1-2 hours, then heating to 85-95° C., stirring for 2-3 hours, and then cooling to room temperature to obtain a fourth acrylic emulsion; S4. Add photosensitizer, defoamer and leveling agent to the fourth acrylic emulsion, protect from light and stir thoroughly, then add neutralizer to adjust pH, and obtain water-based acrylic adhesive.

2. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: The surface cleaning in step 1 is firstly cleaned with deionized water and then with anhydrous ethanol. The cleaning is performed in an ultrasonic device with a cleaning frequency of 20-30 kHz.

3. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: The material of the resin transfer film in step 2 is one of PE, PVC, PET, and PC.

4. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: During the light curing process in step 4, the wavelength of the ultraviolet light is 365nm and the radiation amount is 100-200mW / cm 2 , the curing time is 1-5min.

5. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: The acrylic monomers include acrylic acid, methyl acrylate, methyl methacrylate, lauryl acrylate and tetrahydrofuran methacrylate in a mass ratio of 0.5-1:0.2-0.6:0.3-0.8:0.6-1.2:0.4-0.

8.

6. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: The preparation method of the triazine compound containing vinyl comprises: Weigh 3-methyl-2-butenal and 2-amino-1,3,5-triazine, mix them in toluene, stir them thoroughly until they are uniform, heat them to 80-100° C. under the action of a catalyst, stir them for 3-8 hours, and then perform rotary evaporation to remove impurities to obtain a triazine compound containing a vinyl group.

7. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: In the preparation of the triazine compound containing vinyl, the catalyst is glacial acetic acid, and the added amount is 2%-6% of the mass of 2-amino-1,3,5-triazine; the mass ratio of 3-methyl-2-butenal, 2-amino-1,3,5-triazine and toluene is 1.1-1.4:0.8-1.2:20-50.

8. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: The emulsifier is one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium hexadecyl sulfate, and sodium hexadecylbenzene sulfonate; the crosslinking agent is tripropylene glycol diacrylate or 1,6-hexanediol diacrylate; and the initiator is at least one of sodium persulfate, potassium persulfate, and ammonium persulfate.

9. The process for preparing a composite material based on a resin transfer film according to claim 1, characterized in that: The photosensitizer is at least one of photosensitizer 1173, photosensitizer 819, photosensitizer 184, and photosensitizer 907; the defoamer is at least one of Digo 810, Digo 825, Digo 901W, and Digo 902W; the leveling agent is at least one of BYK-333, BYK-378, and BYK-381; and the neutralizer is triethylamine or ethanolamine.

Citation Information

Patent Citations

  • Method for manufacturing miniLED backlight plate through high-precision single-sided circuit interconnection

    CN115119410A

  • Thermosetting adhesive, adhesive tape and preparation method thereof

    CN116285830A